Measurement of Contrast Sensitivity Using the M&S Smart System II Compared with the Standard Pelli–Robson Chart in Patients with Primary Pterygium - Hilmi, Mohd R; Khairidzan, Mohd K; Azemin, Zulfaezal C; Azami, Muhammad H; Ariffin, Azrin E (UI Scholars Hub, 2018)
Background: Contrast sensitivity (CS) is widely used as a measure of visual function in research and clinical settings. CS is regarded as an important visual parameter, detecting subtle reductions in vision prior to significant reduction in visual acuity. Methods: We examined the agreement between the gold-standard Pelli-Robson chart and a computerized test termed the M&S Smart System II (MSSS-II) in patients with primary pterygium. Ninety-three patients (93 primary pterygium eyes) who visited an ophthalmology clinic were selected. The patients were randomly assessed for CS using the MSSS-II or Pelli-Robson chart. The primary outcome was agreement in log units between these two tests in the assessment of CS in patients with primary pterygium. Results: The mean and standard deviation of CS measurement in the two tests were comparable (1.22 ± 0.56 vs. 1.21 ± 0.57 log units, respectively, p = 0.083). The Bland-Altman plot revealed that the mean difference between the two charts was 0.0016 log units (standard deviation: 0.009 log units) with narrow limits of agreement of -0.0186 to 0.0186. Conclusions: MSSS-II provides an alternative for the clinical assessment of CS using a computerized method that describes the status of visual function in patients with primary pterygium.